Sambatan Traditions: A Portrait of Moderation against the Polarization of Society in the Democratic Party Towards a Year of Harmony - Hamid, Abdul; Wardah, Deda Aenul; Mubarok, Muhamad Sofi (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
As the political year approaches, Indonesia is faced with societal polarization. This phenomenon gives rise to conflict and division between religious communities as conflicts of interest between each group increasingly emerge. This research aims at the Sambatan Tradition as a portrait of religious moderation as a counter narrative to societal polarization in order to create a year of religious harmony. The method used is qualitative research with a descriptive-analytic approach through Robert N. Entman's framing analysis. The results of this research show that the polarization of society ahead of the year of democracy can be broken down by the Sambatan Tradition. The local wisdom values ​​in the Sambat Tradition are relevant to the construction of Al-Qur'an verses which discuss the idea of ​​moderation in upholding peace, tolerance, harmony and mutual cooperation. It is hoped that this research will produce a number of recommendations for the government, society, academics, and the media to explain the polarization of society ahead of the political year according to their respective capacities. The significance of this research is that it offers regulatory ideas that can be implemented by the government as well as being argumentative and constructive for academics.